Forensic Genetics within the Dungeon: The Paradoxical Mosaic of the Brazilian Penal System - Campello, Ricardo Urquizas; Vailly, Joëlle (International Journal of Criminology and Sociology, 2026)
This article deals with the Brazilian penal system, which is seeing on the one hand attempts at ‘modernisation’ through the development of forensic technologies for genetic identification of prisoners, and on the other hand, the persistence of ‘archaic’ correctional institutions. Based on an ethnographic survey, this study analyses prison demographics in relation to the role played by the Brazilian DNA database, which both fails to exonerate convicts and is itself fostered by mass incarceration. It also focuses on the day-to-day procedures for collecting biological material from prisoners, which are often based on discretionary, arbitrary, and even illegal practices, thus establishing links between the permanent threat of prison violence and new genetic identification technologies. Through the sociological allegory of the ‘penal platypus’, it lays the groundwork for a reflection on the re-territorialisation of genetic profiling as it is taking place in Brazil.